Weed Control in Direct Seeded Rice Using Selected Herbicides - Man, Azmi (1984)
Selected herbicides for the control of weeds in direct seeded rice were studied. The phytotoxicity of the herbicides, 2, 4-D amine, 2, 4-DIBE-butachlor, butachlor, benthiocarb and molinate were evaluated in two studies using petri dishes and plastic pots. A field study was also carried out to determine the efficacy of weed control of 2, 4-DIBE-butachlor, butachlor and molinate. 2, 4-D amine and benthiocarb were found to behighly phytotoxic when applied as a preemergent and as an early postemergent. Molinate was safe to apply as a preemergent. All the herbicides evaluated were more toxic when applied during the early postemergent period 14 days after sowing than when applied later at 35 days after sowing.